2022
DOI: 10.3389/fmed.2022.801632
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance With Hypomethylating Agents After Allogeneic Stem Cell Transplantation in Acute Myeloid Leukemia and Myelodysplastic Syndrome: A Systematic Review and Meta-Analysis

Abstract: IntroductionHypomethylating agents (HMAs) seem to have a range of properties favorable to post-allogeneic hematopoietic stem cell transplantation (allo-SCT) maintenance in acute myeloid leukemia (AML) patients.Materials and MethodsThe Embase, MEDLINE, and Cochrane Central Register of Controlled Trials databases were independently searched by two investigators to identify relevant studies published inception to 18 November 2021. These trials compared HMA maintenance to observation following allo-SCT for AML or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A meta-analysis including 14 studies (not limited to randomized controlled trials) showed favorable benefits of post-HSCT HMA maintenance with regard to RFS and OS as well as reduction in rates of chronic GvHD. 109 …”
Section: Post-allogeneic Stem Cell Transplantation-directed Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis including 14 studies (not limited to randomized controlled trials) showed favorable benefits of post-HSCT HMA maintenance with regard to RFS and OS as well as reduction in rates of chronic GvHD. 109 …”
Section: Post-allogeneic Stem Cell Transplantation-directed Maintenancementioning
confidence: 99%
“…A meta-analysis including 14 studies (not limited to randomized controlled trials) showed favorable benefits of post-HSCT HMA maintenance with regard to RFS and OS as well as reduction in rates of chronic GvHD. 109 An important development was the recently reported, encouraging result on the use of eprenetapopt in combination with azacitidine as maintenance therapy in TP53-mutated MDS/AML patients after HSCT. The combination, planned to be given for 12 cycles administered every 4 weeks, led to a median RFS of 12.5 months and OS of 20.6 months (at a median follow-up of 17 months) in 33 patients (79% previously exposed to HMA, 36% with active disease at the time of HSCT, 83% with persistent TP53 mutation at HSCT) who received this maintenance.…”
Section: Hypomethylating Agent-based Therapymentioning
confidence: 99%
“…The median CD34 + cells numbers for transplantation was 7×10 6 /kg (2.86-11.57). The median time to neutrophil engraftment (≥0.5×10 9 /L) after transplantation was 15 (10-23) days, while that of platelet engraftment (≥20×10 9 /L) was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) days (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…However, because LEN can activate NK cells and T cells, it has been reported that the use of LEN may cause severe graft-versus-host disease (GVHD) in patients after allo-SCT ( 10 , 11 ). On the other hand, AZA can accelerate reconstitution of T regulatory cells after transplantation, induce immune tolerance, and reduce the risk of GVHD ( 12 , 13 ). Therefore, we hypothesized that combination of AZA and low-dose LEN could simultaneously provide anti-leukemic activity after transplantation without increasing, overall, the risk of severe GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies had identified the efficacy of maintenance therapy in high-risk AML patients [ 21 23 ], but the results were somewhat controversial. For example, some reported that sorafenib maintenance can decrease relapse and improve LFS after allo-HSCT [ 24 ]; however, MORPHO trial reported that relapse-free survival and OS were comparable between patients with and without gilteritinib maintenance, and gilteritinib maintenance might only improve the survival of patients who were MRD positivity before allo-HSCT [ 25 ].…”
mentioning
confidence: 99%